TRANSFER OF OWNERSHIP OF REGISTERED TRADEMARK RIGHTS BASED ON LAW NUMBER 20 OF 2016 CONCERNING TRADEMARKS AND GEOGRAPHICAL INDICATIONS - Rehulina, Rehulina; Fauziah, Latifah; Afina, Salsabila (LPPM, Universitas Muhammadiyah Riau, 2026)
Intellectual Property is the result of thought in the form of ideas/concepts manifested in the form of discoveries, works of science, literature and art, designs, certain symbols/signs, creations of semiconductor component layouts, and varieties resulting from breeding. Trademark rights are one of the scopes of intellectual property rights. The object of a brand is a sign, whether writing, images, or a combination of writing and images. Trademarks are regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Trademarks are part of Intellectual Property Rights. Trademark rights are a form of compensation and encouragement for people to create. The problem is how the procedure for transferring trademark rights exists. This research is normative and classified as qualitative research. This research uses secondary data sources. Transfer of ownership of trademark rights can be done by inheritance, will, waqf, grant, or license agreement. The transfer of trademark rights is based on an authentic deed made by a Notary. Applications for transfer can be made online through the official website of the Directorate General of Intellectual Property Rights by uploading the required documents. This application for the transfer of trademark ownership creates legal certainty and protection for both the original and subsequent owners, based on the legal transfer. Transfers of registered trademark rights must be registered with the Directorate General of Intellectual Property Rights, accompanied by supporting documentation.